The Legal and Psychological Challenges of Female Prisoners in Pakistan - Hassan, Syed Saqlain Ul; Zameer, Asma; Haider, Syed Zulqarnain; Sajid, Saima (Pakistan Journal of Humanities and Social Sciences, 2023)
In Pakistan, female prisoners experience a range of difficulties and hindrances that have an impact on both their legal rights and psychological well-being. This study addresses the legal and psychological problems that Pakistani female inmates experience and investigates their causes and effects. A thorough overview of the situation of female prisoners in Pakistan is provided by the research using both qualitative and quantitative data from diverse sources. To solve these problems and better help female convicts, the essay also makes several recommendations to stakeholders and legislators.